Comparison of Yizhiqingxin formula extraction methods and their pharmacodynamic differences - Wei, Wei; Pei, Hui; Ma, Li-Na; Zheng, Rui; Huang, Qiao-Yi; Chang, Su-rui; Cao, Yu; Li, Hao (Frontiers in Neuroscience, 2023)
Objectives This study compared different extraction methods of Yizhiqingxin formula (YQF) and its neuroprotective effects based on pharmacodynamic indices such as learning and memory ability, brain tissue histopathology and morphology, and inflammatory factor expression in a mouse model of Alzheimer’s disease (AD). Methods The pharmaceutical components of YQF were extracted using three extraction processes, and the components were analyzed by high performance liquid chromatography. Donepezil hydrochloride was used as a positive control drug. Fifty 7–8-month-old 3 × Tg AD mice were randomly divided into three YQF groups (YQF-1, YQF-2, and YQF-3), a donepezil group, and a model group. Ten age-matched C57/BL6 mice were used as normal controls. YQF and Donepezil were administered by gavage at a clinically equivalent dose of 2.6 and 1.3 mg⋅kg–1⋅d–1, respectively, with a gavage volume of 0.1 ml/10 g. Control and model groups received equal volumes of distilled water by gavage. After 2 months, the efficacy was evaluated using behavioral experiments, histopathology, immunohistochemistry, and serum assays. Results The main components in YQF are ginsenoside Re, ginsenoside Rg1, ginsenoside Rb1, epiberberine, coptisine chloride, palmatine, berberine, and ferulic acid. YQF-3 (alcohol extraction) has the highest content of active compounds, followed by YQF-2 (water extraction and alcohol precipitation method). Compared to the model group, the three YQF groups showed alleviated histopathological changes and improved spatial learning and memory, with the effect in YQF-2 being the most significant. YQF showed protection of hippocampal neurons, most significantly in the YQF-1 group. YQF significantly reduced Aβ pathology and tau hyperphosphorylation, decreased expressions of serum pro-inflammatory factors interleukin-2 and interleukin-6 as well as serum chemokines MCP-1 and MIG. Conclusion YQF prepared by three different processes showed differences in pharmacodynamics in an AD mouse model. YQF-2 was significantly better than the other extraction processes in improving memory.